2017
DOI: 10.1007/s00392-017-1166-2
|View full text |Cite
|
Sign up to set email alerts
|

Radial access protects from contrast media induced nephropathy after cardiac catheterization procedures

Abstract: Our study shows that cardiac catheterization using radial access bears significantly lower risk of AKI than cardiac catheterization via femoral access. The advantage of radial access in acute coronary syndrome regarding morbidity and mortality could partly be explained by the here demonstrated reduced risk for AKI. Thus, radial access should be preferred in patients at risk for AKI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 35 publications
0
19
0
1
Order By: Relevance
“…9 Given differences in baseline patient comorbid conditions and the procedural risks of coronary angiography, it is intuitive to expect a higher AKI rate following CM exposure with coronary angiography compared to CECT. 21,22 Numerous studies of patients undergoing coronary angiography have demonstrated AKI rates of w13%, which exceeds the average AKI rates of 5% to 6% associated with intravenous CM exposure. 13,[23][24][25] One conclusion of these results, although controversial, is that intra-arterial delivery of CM is more nephrotoxic compared to intravenous administration.…”
Section: Comparison Of Cin With Intra-arterial and Intravenous Contramentioning
confidence: 98%
“…9 Given differences in baseline patient comorbid conditions and the procedural risks of coronary angiography, it is intuitive to expect a higher AKI rate following CM exposure with coronary angiography compared to CECT. 21,22 Numerous studies of patients undergoing coronary angiography have demonstrated AKI rates of w13%, which exceeds the average AKI rates of 5% to 6% associated with intravenous CM exposure. 13,[23][24][25] One conclusion of these results, although controversial, is that intra-arterial delivery of CM is more nephrotoxic compared to intravenous administration.…”
Section: Comparison Of Cin With Intra-arterial and Intravenous Contramentioning
confidence: 98%
“…Removing individual studies did not result in significant deviation of the pooled OR (all P < 0.0001) for the occurrence of AKI. Subgroup analysis (Figure (B)) demonstrated a gradient in the impact of TRA according to study design, with higher benefit accrued in retrospective studies than across studies with propensity‐score matching, as compared with the relatively lower treatment effect (namely 13%) observed in the randomized AKI‐MATRIX trial …”
Section: Resultsmentioning
confidence: 99%
“…When weighing the interests of safety vs. independence, it is mandatory to have specific scientific knowledge about postoperative driving impairments following invasive medical procedures. Even if the transradial approach is increasingly used in CAG and BRT is very likely not affected by it, the transfemoral access in CAG is still widely used [ 24 ]. We, therefore, feel our results are still of relevance even though the transradial access in CAG is gaining ground.…”
Section: Discussionmentioning
confidence: 99%